Nemoral deciduous forests under climatic extremes – phytosociological studies along climatic gradients in SW Romania - Indreica, Adrian; Teodosiu, Marius; Petritan, Ana-Mary; Oder, Veronika; Kasper, Jan; Bergmeier, Erwin; Leuschner, Christoph; Gailing, Oliver; Hohnwald, Stefan; Wildhagen, Henning; Walentowski, Helge (Transilvania University Press, Brasov, 2019)
Based on studies on stand structure, plant community composition and tree ecology across a climate gradient in western Romania from beech-dominated to oak-dominated forests, we are investigating how climate warming in 50-60 years would affect forest ecosystem structure, the vitality of important tree species, and the provision of energy wood from nemoral broad-leaved forests. The aim is to identify and characterize the tipping-points from mesic-hygrophilous, dark shady deciduous forests of Fagetalia sylvaticae to thermophilous, light deciduous forests of Quercetalia pubescenti-petraeae forests by using data from the Romanian Forests Vegetation Database. We applied non-metric multidimensional scaling, and indicator species analysis to evaluate ecologically three groups of relevés: (1) beech dominated forests, (2) mixed oak-hornbeam forests and (3) thermophilous oak dominated forests. We analysed spatial distribution of high order syntaxa, degree of warm thin terms of mean Ellenberg indicator values and number of thermophilous species, site differentiation in terms of altitude, aspect, temperature and precipitation. Our findings indicate that the gradient analysis could be performed on transects starting from 600 m downhill to 200 m, representing gradients of decreasing mean annual precipitation (from 800 to 600 mm), increasing temperature (+2-3°C) and increasing risk of drought stress as a proxy for climate warming. We proposed the following selection criteria: (i) near-natural deciduous forests; (ii) coherent and widely undisturbed woodland areas; (iii) sufficient elevational sequences; (iv) intermediate level of hygrotope (soil moisture regime) and trophotope (soil nutrient regime); (v) same slope aspect (southeastern direction); and (vi) sufficient distance (50-60 km) to each other
Keywords: species niche; nemoral forests; climatic gradients; multiplicative regression; indicator species